Children's diurnal cortisol output and temperament in two different childcare settings at 2 and 3.5 years of age - Tervahartiala Katja; Kortesluoma Susanna; Pelto Juho; Ahtola Annarilla; Karlsson Hasse; Nolvi Saara; Karlsson Linnea (United States, 2022)
Prior research suggests that child temperament may play an important role in early childhood stress regulation. We compared children's diurnal cortisol and the association between cortisol and temperament in two different childcare settings. Cortisol was measured from saliva samples over 2 days in children (N = 84) attending out-of-home childcare and in children (N = 27), who were cared for at home at the age of 3.5 years. There was no difference between the childcare groups in total diurnal cortisol. However, of the individual measurements, afternoon cortisol levels were higher in the out-of-home childcare group during their childcare day when compared with their home day. Child temperament was not associated with total diurnal cortisol. Comparison with our prior measurements showed that the association between temperamental surgency/extroversion and total diurnal cortisol diminished along with the child age from 2 to 3.5 years in both childcare settings. This may indicate that more extroverted children are physiologically more reactive to environmental stimuli when they are younger, but this association does not appear as the children develop. Our results further suggest that the afternoon hours in the out-of-home childcare may be demanding and accelerate the hypothalamus–pituitary–adrenal axis activation in young children independent of their age.